Transporting and implementing a caregiver-mediated intervention for toddlers with autism in Goa, India: evidence from the social ABCs - Brian, Jessica A.; Dowds, Erin M.; Bernardi, Kate; Velho, Andre; Kantawalla, Mahera; de Souza, Nandita (Frontiers in Rehabilitation Sciences, 2024)
Autism is a global health priority with an urgent need for evidence-based, resourceefficient, scalable supports that are and feasible for implementation in low-and middle-income countries (LMICs). Initiating supports in the toddler years has potential to significantly impact child and family outcomes. The current paper describes the feasibility and outcomes associated with a Canadian-developed caregiver-mediated intervention for toddlers (the Social ABCs), delivered through a clinical service in Goa, India. Methods. Clinical staff at the [BLINDED CENTRE] were trained by the Canadian program development team and delivered the program to families seen through their clinic. Using a retrospective chart review, we gathered information about participating families and used a pre-post design to examine change over time. Results. Sixty-four families were enrolled (toddler mean age = 28.5 months; range: 19 -35), of whom 55 (85.94%) completed the program. Video-coded data revealed that parents learned the strategies (implementation fidelity increased from M = 45.42% to 76.77%, p < .001, with over 90% of caregivers attaining at least 70% fidelity). Toddler responsivity to their caregivers (M = 7.00% vs. 46.58%) and initiations per minute (M = 1.16 vs. 3.49) increased significantly, p's < .001. Parents also reported significant improvements in child behaviour/skills (p < .001), and a non-significant trend toward reduced parenting stress (p = .056). Discussion. Findings corroborate the emerging evidence supporting the